Respuesta :

gmany

The point-slope form:

[tex]y-y_1=m(x-x_1)[/tex]

m - slope

(x₁, y₁) - the point

The formula of a slope:

[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]

We have the points (5, 4) and (2, -2). Substitute:

[tex]m=\dfrac{-2-4}{2-5}=\dfrac{-6}{-3}=2[/tex]

[tex]y-4=2(x-5)[/tex] - point-slope form

[tex]y-4=2x-10[/tex]        add 4 to both sides

[tex]y=2x-6[/tex]  - slope-intercept form

[tex]y=2x-6[/tex]      subtract 2x from both sides

[tex]-2x+y=-6[/tex]      change the signs

[tex]2x-y=6[/tex]   - standard form

-------------------------------------------------------------------

From the table we have two points (1, 3) and (2, 7). SubstituteL

[tex]m=\dfrac{7-3}{2-1}=\dfrac{4}{1}=4[/tex]

[tex]y-3=4(x-1)[/tex]   - point-slope form

[tex]y-3=4x-4[/tex]     add 3 to both sides

[tex]y=4x-1[/tex]    - slope-intercept form

[tex]y=4x-1[/tex]      subtract 4x from both sides

[tex]-4x+y=-1[/tex]     change the signs

[tex]4x-y=1[/tex]    - standard form